Management of adverse events related to endoscopic resection of upper gastrointestinal neoplasms: Review of the literature and recommendations from experts. (17th April 2019) - Yamamoto, Yorimasa; Kikuchi, Daisuke; Nagami, Yasuaki; Nonaka, Kouichi; Tsuji, Yosuke; Fujimoto, Ai; Sanomura, Yoji; Tanaka, Kyosuke; Abe, Seiichiro; Zhang, Shuo; De Lusong, Mark Anthony; Uedo, Noriya
Abstract : Prevention therapy is recommended for lesions >1/2 of the esophageal circumference. Locoregional steroid injection is recommended for lesions >1/2–3/4 of the esophageal circumference and oral steroids are recommended for lesions >1/2 of the subtotal circumference. For lesions of the entire circumference, oral steroid combined with injection steroid is considered. Endoscopic balloon dilatation (EBD) is the first choice of treatment for stricture after esophageal endoscopic submucosal dissection (ESD). Radical incision and cutting or self‐expandable metallic stent can be considered for refractory stricture after EBD. In case of intraoperative perforation during esophageal ESD, endoscopic clip closure should be initially attempted. Surgery is considered for treatment of delayed perforation. Current standard practice for prevention of delayed bleeding after gastric ESD includes prophylactic coagulation of vessels on post‐ESD ulcers and giving proton pump inhibitors. Chronic kidney disease stage 4 or 5, multiple antithrombotic drug use, anticoagulant use, and heparin bridging therapy are high‐risk factors for delayed bleeding after gastric ESD. Intraoperative perforation during gastric ESD is initially managed by endoscopic clip closure. If endoscopic clip closure is difficult, other methods such as over‐the‐scope clip (OTSC), polyglycolic acid (PGA) sheet shielding etc. are attempted. Delayed perforation usually requires surgical intervention, but endoscopic closure by OTSC or PGA sheet may be considered. Resection of three‐quarters of the circumference is a risk factor for stenosis after gastric ESD. Giving prophylactic local steroid injection and/or oral steroid is reported, but effectiveness has not been fully verified as has been done for esophageal stricture. The main management method for gastric stenosis is EBD but it may cause perforation.